Modernists at Odds : Reconsidering Joyce and Lawrence - Knowles, Sebastian D. G. (Sebastian David Guy); Lusty, Heather L.; Kochis, Matthew J. (Book collections on Project MUSE., 2015)
This collection, curated by Matthew J. Kochis and Heather L. Lusty, comprises the first in-depth exploration of the resonances between James Joyce and D.H. Lawrence, whom scholars have traditionally viewed as polar opposites. The essays consider themes such as sexuality, nature, religion, and censorship, and show that there are many intersections among the issues that most concerned them both.